Effects of Unilateral Maxillary Premolar Extraction on Smile Aesthetics: A Retrospective Study - Safavi, Seyed Moahammad Reza; Dehghani Soltani, Anahita; Motamedian, Saeed Reza; Akbarzadeh Baghban, Alireza; Ghaffari, Samin (Galen Medical Journal, 2025)
Background: Unilateral maxillary premolar extraction (UMPE) has been recommended for the orthodontic treatment of specific dental asymmetries. This study has aimed to compare the extraction side and non-extraction side within the same patient to assess the impact of UMPE on specific dental and aesthetic outcomes. Materials and Methods: In this retrospective investigation at department of orthodontics, school of Dentistry, Shahid Beheshti University of Medical Sciences (SBMU), post treatment documents of 40 patients, who underwent UMPE in their completed orthodontic treatments, were selected. Upper dental midline, smile arc and number of visible teeth in final smile photographs was assessed. Evaluations were analyzed using SPSS 18. Results: Analyses showed a positional deviation of upper dental midline in 90% of patients by average of 1.0±0.5 mm, the angular deviation of dental midline in 87.5% of patients toward the extraction side by average of 0.83°±0.27° and an elevated smile arc for 0.43 mm in extraction side. Moreover, the evaluations showed a mean of 5 and 4.52 visible teeth in the non-extraction and the extraction sides, respectively. Conclusion: The current study showed that in the treatment with UMPE the smile indices can be end very close to absolute symmetry and the asymmetries that still exists are negligible and will not affect the aesthetic results of the treatment.